Investigations of Energy Characteristics of Alkaline Electrolyzers with Conic Electrodes - V. V. Ivashechkin; N. P. Matveyko (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper presents results of the experimental research that studies influence of geometric characteristics of conic electrodes on electrolyzer productivity.Methodology and calculation example are given in the paper